Fmoc-diphenylalanine gelating nanoarchitectonics: A simplistic peptide self-assembly to meet complex applications - Wang, Yunxiao; Geng, Qiang; Zhang, Yan; Adler-Abramovich, Lihi; Fan, Xinyuan; Mei, Deqing; Gazit, Ehud; Tao, Kai (Journal of colloid and interface science, 2023)
As the representative self-assembling peptide with the high probability of industrialization, Fmoc-FF self-assembly has aroused increasing attention, giving rise to bioinspired, supramolecular functional material alternatives for biomedical, bio-machine interfacing and industrial applications. Especially, the studies of Fmoc-FF self-assembly & hydrogelation are truly and extensively interdisciplinary, encompassing a wide variety of subjects with significant bio-inspiration including chemistry, materials science, physics, biology, medicine, nanotechnology as well as advanced device manufacturing, and require communications and collaborations between scientists from different fields and backgrounds. Therefore, there is no doubt that the progress of Fmoc-FF self-assembly will provide new ideas for relevant research directions and will greatly contribute to the development of the referred disciplines. Considering the incessant studying and increasing amount of publications, we may witness the development of implantable or wearable devices based on Fmoc-FF hydrogelation, which can integrate multiple functions such as in situ monitoring, real-time feedback, therapeutic treatment, self-powering, self-healing, biodegradation and other desired functions. [Display omitted] 9-fluorenylmethoxycarbonyl-diphenylalanine (Fmoc-FF), has been has been extensively explored due to its ultrafast self-assembly kinetics, inherent biocompatibility, tunable physicochemical properties, and especially, the capability of forming self-sustained gels under physiological conditions. Consequently, various methodologies to develop Fmoc-FF gels and their corresponding applications in biomedical and industrial fields have been extensively studied. Herein, we systemically summarize the mechanisms underlying Fmoc-FF self-assembly, discuss the preparation methodologies of Fmoc-FF hydrogels, and then deliberate the properties as well as the diverse applications of Fmoc-FF self-assemblies. Finally, the contemporary shortcomings which limit the development of Fmoc-FF self-assembly are raised and the alternative solutions are proposed, along with future research perspectives.